Association between alcohol intake and overweight and obesity: a systematic review and dose-response meta-analysis of 127 observational studies. Issue 29 (17th October 2022) - Golzarand, Mahdieh; Salari-Moghaddam, Asma; Mirmiran, Parvin
Abstract: Several studies have assessed the relationship between alcohol intake and overweight/obesity; however, the reported results are inconsistent. Therefore, the present systematic review and dose-response meta-analysis of observational studies was designed to investigate the association between alcohol intake and general and abdominal obesity among the adults. Literature search was conducted in the PubMed/Medline and Web of Science databases up to August 2020. Odds ratio (OR), risk ratio (RR), or hazard ratio (HR) with 95% confidence interval (95% CI) were used to pool effect size. To conduct dose-response meta-analysis, amount of alcohol intake was classified into three categories including light (<14 g/d), moderate (14–28 g/d), and heavy (>28 g/d). In the present study, 127 eligible studies were included. In cohort studies, there was no significant association between alcohol drinking and risk of overweight (OR: 0.93, 95% CI: 0.46 to 1.89), obesity (OR: 0.84, 95% CI: 0.52 to 1.37), overweight/obesity (OR: 1.15, 95% CI: 0.84 to 1.58), and abdominal obesity (OR: 1.13, 95% CI: 0.90 to 1.41). In cross-sectional studies, alcohol intake was associated with the increased odds of overweight (OR: 1.11, 95% CI: 1.05 to 1.18), overweight/obesity (OR: 1.23, 95% CI: 1.11 to 1.37), and abdominal obesity (OR: 1.19, 95% CI: 1.09 to 1.29); but not obesity (OR: 1.03, 95% CI: 0.95 to 1.12). Results of dose-response analysis indicated that heavy alcohol drinking was positively associated with odds of overweight (OR: 1.12, 95% CI: 1.01 to 1.24), overweight/obesity (OR: 1.32, 95% CI: 1.16 to 1.51), and abdominal obesity (OR: 1.25, 95% CI: 1.12 to 1.38) compared to non- or light alcohol drinking. There was no publication bias among studied on outcomes of interest. In conclusion, our results revealed alcohol drinkers, especially heavy alcohol drinkers, had increased odds of overweight, overweight/obesity, and abdominal obesity than non-alcohol drinker or light alcohol drinkers among cross-sectional studies but not cohort studies.